A novel H2O2 responsive supramolecular hydrogel for controllable drug release. Issue 3 (5th January 2017) - Ren, Chunhua; Chu, Liping; Huang, Fan; Yang, Lijun; Fan, Huirong; Liu, Jianfeng; Yang, Cuihong
Abstract : We reported a peptide-based supramolecular hydrogel possessing a gel–sol phase transition triggered by H2 O2 . Abstract : Due to the important significance of hydrogen peroxide (H2 O2 ) in physiology, aging and disease in living organisms, tremendous effort has been devoted to develop H2 O2 responsive materials for the detection of its over production or for controlled drug release. However, it is still challenging to develop H2 O2 responsive supramolecular hydrogels. In this study, we designed and synthesized a novel H2 O2 responsive peptide hydrogelator bearing the thiazolidinone group. A supramolecular hydrogel based on peptide self-assembly was prepared through a heating–cooling process and its gel–sol phase transition could be triggered by the removal of thiazolidinone groups upon H2 O2 oxidization. The excellent H2 O2 responsive property of the supramolecular hydrogel was investigated by LC-MS, rheology and TEM. A drug release study in vitro demonstrated that the gel–sol phase transition could be applied for releasing gemcitabine sustainedly and controllably. Our study could provide a new way for the design of H2 O2 responsive materials and hold great potential in the application of anticancer drug delivery.